Synthesis and Spectroscopic Studies of Metal Complexes with Schiff Bases Derived from 2-[5-(Pyridin-2-Ylmethylene)-Amino] 1,3,4-Thiadiazol-2-Yl-Phenol - Shaalan, Naser; Akram, Evon; Adil, Dina; Ali, Ali A. (Al-Nahrain Journal of Science, 2018)
Herein, we show the preparation and the characterization of new metal complexes by using a Schiff base ligand 2-[5-(Pyridin-2-ylmethylene)-amino] 1,3,4-thiadiazol-2-yl-phenol (L) with the metals Co(II), Ni(II), Cu(II) and Zn(II). This Schiff base ligand was synthesized via condensing [2-pyridine carboxaldehyde] with [2-amino-5-phenyl-1,3,4-thiadiazol] in an alcoholic solution. For preparing complexes, two tetradentate Schiff bases ligand were employed with two metal ions of Co2+, Ni2+, Cu2+ and Zn2+ as dinuclear formula M2L2. The synthesized ligand and its metal complexes were well characterized using FTIR, UV-Vis absorption, elemental analysis, thermal analysis, 1H-NMR, and mass spectroscopy. Based on these characterizations, the chemical structures of the ligand and the metal complexes were confirmed. Furthermore, the electronic and magnetic properties of the prepared metal complexes were clearly understood.